Development Of Teaching Book For Dyslexia Children With Learning Style Intervention Assisted By Audio Visual Media At Elementary School - Khasanah, Uswatun; Murtono, Murtono; Fathurohman, Irfai (Universitas Muria Kudus, 2022)
The purpose of the study wasto designof developing teaching books for dyslexia through learning style intervention assisted by audio-visual media for elementary school students. This research is Research and Development. Data collection uses a needs questionnaire, expert validation sheets, student learning outcomes tests, interviews, observations and documentation. Data analysis techniques were carried out qualitatively and quantitatively. The subjects in this study were dyslexic students at SDN Brambang Karangawen Demak with a total of three of the third grade students. The result of the study is that the design of developing audio-visual-assisted teaching books has characteristics, including the use of good and easy-to-understand language, the presentation of the teaching books equipped with pictures and videos, and the contents of the teaching books describing the author's ideas. The teaching book development product consists of three parts, namely the introduction which contains of the title page or book cover, the introduction, and the table of contents. The section consists ofletter introducing, words repeating, writing, drawing, direction and story. The closing section contains reflection. The conclusion of study is the design of the teaching book is adapted to the characteristics of a good teaching book and the needs of dyslexia students.